Pemberdayaan Ekonomi Kreatif Berbasis Kearifan Lokal dalam Meningkatkan Daya Saing Usaha Pengrajin Home Craft Lipa Sabbe di Kota Makassar - Yuniarti Yuniarti; Fitriaty Pangerang; Rastina Rastina (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance production capacity and business competitiveness through the application of appropriate technology and the strengthening of creative economy–based business management. The program was implemented through training, technology adoption, and mentoring activities involving five ethnic home craft artisans producing Lipa Sabbe textiles in Makassar City. Evaluation instruments included observation sheets assessing production processes and product quality, mentoring logbooks, simple financial record-keeping formats, visual documentation, and summaries of social media activities. The data were analyzed using descriptive comparative analysis. The results indicate that production quantity nearly doubled, product defect rates decreased from 15–20% to less than 5%, and production time efficiency improved by approximately 50%. In addition, the regularity of financial transaction records increased nearly threefold, monthly revenue rose by 20–30%, and digital marketing activities became more effective, as reflected by a 60% increase in consumer engagement through social media platforms. The program also contributed to community empowerment, particularly among housewives, and supported the preservation of local culture through the utilization of Lipa Sabbe woven fabrics as economically valuable craft products. Overall, these findings demonstrate that the program effectively improved community welfare, strengthened cultural identity, and expanded market access within the creative economy sector.